Primary retroperitoneal teratoma in a young woman: a case report - Nadeem Iqbal; Aitzaz Khan, Mahnoor; Khalil, Ibrahim; Ali, Adnan; Aleem, Haris; Bin Nusrat, Nadeem (Journal of the Pakistan Medical Association, 2023)
Teratomas are usually seen in gonads but they do occur in other extra gonadal regions such as sacrococcygeal region, mediastinum, head and neck, and retroperitoneum. Rarely in the retroperitoneal area, such tumours mostly develop in the pararenal area and usually on the left side. They have bimodal presentation at the age of six months and then in early adulthood. They originate from the germ cells that have failed to migrate to normal anatomical destinations. Many of such patients are diagnosed incidentally. Here, we report a case of symptomatic primary retroperitoneal mature teratoma in a young lady managed at Pakistan kidney and Liver Institute, Lahore. Key Words: Benign Mature Cystic Teratoma; Kidney; Surgery; Retroperitoneal teratoma.